Determination of Spirotetramat in Complex Matrices Combining QuEChERs and Solid Phase Extraction Followed by High Performance Liquid Chromatography - Wu, Junxue; Wang, Chengju; Wang, Kai; Wang, Baitao; Zhang, Yun; Zhang, Hongyan (Asian Journal of Chemistry, 2015)
A new sample preparation procedure combining QuEChERs and solid phase extraction was optimized for the determination at trace levels of spirotetramat in complex matrices by high performance liquid chromatography with ultraviolet detector (HPLC-UVD). Seven foods (tea, agaric, celery, leek, citrus, soybean and walnuts) were selected as complex matrices for validating this new method. The target analyte was extracted with acetonitrile and cleaned up by Cleanert TPH and the recoveries of spirotetramat in seven foods were in range of 76.9 to 106.7 % with relative standard deviation of 1.1 to 10.8 % at three spiking levels. The limit of quantification of spirotetramat in tea, agaric, celery, leek, citrus, soybean and walnuts were 0.1, 0.1, 0.2, 0.2, 0.1, 0.1 and 0.05 mg/kg, respectively. The proposed method was applied to determine the residue of spirotetramat in seven samples from regional retailers in Beijing and no spirotetramat was detected.